2020
DOI: 10.3354/meps13375
|View full text |Cite
|
Sign up to set email alerts
|

Stress-on-stress responses of a marine mussel, Perna canaliculus: food limitation reduces the ability to cope with heat stress in juveniles

Abstract: The marine environment is ever-changing, with daily and seasonal variations in factors such as food availability and seawater temperature. These stressors can affect physiological processes in aquatic organisms, resulting in sub-lethal or lethal consequences. This study assessed the effects of food limitation (i.e. fasting) on heat-stress responses in juveniles (~1.3 mm in shell length) of the green-lipped mussel Perna canaliculus. Fasting for up to 24 h did not have a significant effect on oxidative damage (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…The emersion times used in this study are representative of a typical exposure period for an intertidal P. canaliculus (1 h), an exceptional low tide event (5 h), and an artificial emersion time which would represent a common transport time for mussel spat from hatchery to the grow-out farms (20 h). It should be noted that the juvenile mussels used in this study are hatchery produced from subtidal mussel populations (farmed); the results shown here might vary from the potential stress response of wild spat which may have previously experienced emersion [ 36 ] and associated stressors, with the potential to either increase [ 37 ] or reduce [ 32 ] subsequent stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The emersion times used in this study are representative of a typical exposure period for an intertidal P. canaliculus (1 h), an exceptional low tide event (5 h), and an artificial emersion time which would represent a common transport time for mussel spat from hatchery to the grow-out farms (20 h). It should be noted that the juvenile mussels used in this study are hatchery produced from subtidal mussel populations (farmed); the results shown here might vary from the potential stress response of wild spat which may have previously experienced emersion [ 36 ] and associated stressors, with the potential to either increase [ 37 ] or reduce [ 32 ] subsequent stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Macromolecule extractions (protein, lipid and DNA) for determination of oxidative damage in juvenile P. canaliculus were performed according to Delorme et al [ 32 ] In brief, total protein was extracted on ice by adding 900 µL of ice-cold enzyme extraction buffer (100 mM potassium phosphate [pH 7.5] containing 50 mM NaCl, 0.1 mM Na2EDTA, 1% polyvinylpyrrolidone−40, 2 mM phenylmethylsulfonyl fluoride and 0.1% TritonX−100) and homogenising for 30 s at 1500 rpm (1600 MiniG ® , SPEX ® ) using zirconia/silica beads and a pre-chilled cryo-block (SPEX ® ). The samples were then centrifuged for 15 min at 17,000× g at 4 °C and the supernatant (i.e., protein extract) purified using ultrafiltration and purification columns (AMICON).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cumulation of adverse environmental conditions can weaken mussels and make them more susceptible to mortality from conditions that they are able to cope with under normal circumstances (Delorme et al 2020). This is also dependent on the health status of the mussel.…”
Section: Environmental Conditionsmentioning
confidence: 99%